HUKUM PENGGUNAAN ALAT KONTRASEPSI DALAM PRESPEKTIF AGAMA ISLAM - Zamzam Mustofa; Nafiah Nafiah; Dyna Prasetya Septianingrum (MA'ALIM: Jurnal Pendidikan Islam, 2020)
This study examines the legal use of contraceptives in Islam. With the aim of strengthening the position of Islamic law in the use of contraceptives. The process of collecting data is done through a library research, interviews, and the results of interviews that have been analyzed. Contraception is defined as a tool used in preventing pregnancy. There are two types of contraceptives commonly used to regulate, limit and even stop pregnancy, namely traditional methods of contraception such as the azal system, calendar, thermal, and so on. While modern methods of contraception such as hormonal contraception, Pills, Injections, Implantation KB, IUD, condoms and mantab contraception or vasectomy / tubectomy. Based on an analysis of Islamic law the use of contraceptives was disputed by jurists. Regarding the use of contraceptives, the majority of scholars allow as long as the use of contraceptives is not permanent. While contraception is permanent (vasectomy / tubectomy), the majority of scholars forbid it. Thus it is clear that the essence of the KB program's task is to significantly reduce birth rates.